(untitled) (Al-Academy, 2024)
This study delves into the integration of the philosophical concepts of space and time within the context of Diriyah’s rich cultural and historical backdrop, aiming to leverage these concepts as foundational pillars for innovative artistic design within the visual arts and design domain. It adopts a hybrid methodology that combines descriptive and analytical techniques for its theoretical framework with experimental approaches for practical application. The outcomes underscore the feasibility and potential of melding space and time philosophies to foster unique design ideas for installation art, thereby enriching the visual arts and design landscape. Some recommendations were presented including engaging deeply with philosophical themes such as the essence of space and time. This research not only contributes to the artistic valorization of Diriyah’s heritage within the framework of Saudi Arabia’s Vision 2030 but also propels forward the discourse on integrating architectural heritage with contemporary art practices.